Leptospiral meningoencephalitis in a raccoon dog. (November 2021) - Yamashita, Risako; Yoshida, Toshinori; Kobayashi, Mio; Uomoto, Suzuka; Shimizu, Saori; Takesue, Keisuke; Maeda, Natsuno; Hara, Erika; Ohshima, Kanami; Zeng, Wen; Takahashi, Yasunori; Ikeuchi, Aoi; et al.
Neuroleptospirosis is a rare disease caused by pathogenic Leptospira interrogans in humans; however, it has not been fully studied in animals. A young wild raccoon dog was found convulsing in the recumbent position and died the next day. Histologic examination revealed nonsuppurative meningoencephalitis in the cerebrum, cerebellum, midbrain, and medulla oblongata. The lesions consisted of mixed infiltrates of Iba1-positive macrophages and CD3-positive T cells, with a small number of CD79α-positive B cells and myeloperoxidase-positive neutrophils. In the frontal cortex, perivascular cuffs and adjacent microglial nodules were distributed diffusely, especially in the molecular layer. Glial nodules were comprised of Iba1- and myeloperoxidase-positive activated microglia. Immunohistochemistry revealed leptospires in mononuclear cell perivascular cuffs, but not in glial nodules. Neuroleptospirosis was accompanied by Leptospira -related nonsuppurative interstitial nephritis, pulmonary edema and hemorrhage, and coronary periarteritis, as well as Toxocara tanuki in the small intestine and nonspecific foreign-body granulomas in the lungs and stomach.